ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS PADA PERUSAHAAN JASA PERHOTELANYANG TERDAFTAR DI BURSA EFEK INDONESIA - Purba, Imelda R.; Purba, Betniar (UNIKA Santo Thomas, 2020)
This study aims to analyze the ability of the hotel services company in the Indonesia Stock Exchange to generate profits with the total assets available. This ability is seen from the value of ROA and the value of ROE (return on investment of shareholders). The benefit of this research is to provide information material to investors in making investment decisions. This study uses secondary data, namely the Financial Statements of Hospitality Service Companies listed on the Indonesia Stock Exchange for the period 2014-2018 which can be accessed via the internet. The data analysis technique used in this research is ratio analysis. The ratio analysis used is the profitability ratio, which is represented by Return On Assets (ROA) and Return On Equity (ROI). The results showed that in these company profitability ratios from 2014 to 2018, in general, several companies experienced a decline, which indicates that the company's profitability ratio is getting less good. Of the 5 hotel services companies studied, the authors also concluded that the Destination Company Tirta Nusantara Tbk. (PDES) is a hotel service company that has the best profitability ratio. This means that this company is a hotel service company listed on the Indonesia Stock Exchange that has the best financial performance. Meanwhile, Golden Eagle Energy Tbk. (SMMT) is a hotel service company that has the worst profitability ratio. Based on the research results, it is recommended that the management of the hotel services listed on the Indonesia Stock Exchange be able to maintain and even improve their performance from year to year. The company is also expected to be able to manage its assets properly so that the company's performance will increase and further research uses all the ratios in operational variables to assess the company's financial performance.